EVALUASI DAN ANALISIS PENGETAHUAN GURU TERHADAP MEDIA MICROBLOG SEBAGAI KONTEN FORMATIF - Dewi Jayana (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2022)
The research was conducted directly in the field by observing and evaluating teachers through interviews with teachers at SMAN 6 Takengon. Evaluation of the media that has been applied by the teacher. This study aims to evaluate the needs of learning media applied by teachers and inform that microblog media will be very effective and efficient for teachers to apply during the learning process. The problem found that teachers were constrained by internet network signals and did not understand the use of media, and some teachers only applied handbooks to students. In this study used qualitative research and descriptive analysis methods, data collection in research through interviews containing a list of questions and supported by a questionnaire in the form of a questionnaire that was submitted directly to the teacher. Data collection is also done through a communication platform, namely WhatsApp. From the research conducted, most teachers have not applied the right media to arouse students' motivation and creativity as an evaluation.